Patient Pathways and Diagnostic Value in Sierra Leone - Fatmata Bah; Eva Vernooij; Alice Street (Medicine Anthropology Theory, 2021)
What is the value of a diagnostic test? Most obviously for primary healthcare settings, laboratory tests can inform clinical decision making about treatment and patient management. Their predominant value in this context is therefore medical. But what about when that healthcare setting is chronically under-resourced, healthcare workers (including laboratory workers) are underpaid, and government supply chains fail to deliver basic laboratory supplies? In this contribution to the Field Notes section, we describe a Community Health Centre (CHC) in Sierra Leone where such conditions have given rise to a quasi-private laboratory service within the public health facility. Through detailed ethnographic description of patients’ diagnostic pathways through the facility, we examine and assess the impact on patient care when the medical and economic value of diagnostic tests diverge.